AUJMSR 2021
DOI: 10.25259/aujmsr_1_2021
|View full text |Cite
|
Sign up to set email alerts
|

Stress among doctors: A cross-sectional study in a tertiary care hospital, North India

Abstract: Objectives: The objectives of the study were as follows: 1. To study the prevalence of stress among doctors. 2. To find the association of stress and its risk factors. Materials and Methods: Institution based cross-sectional study was conducted in the tertiary hospital of Punjab. Pre-validated questionnaire was used to assess the demographic variables and stress factors. Perceived Stress Scale-10 was used to assess the stress levels among the doctors. Results: Of the 203 participants, females (54.7%) outnu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The findings of the present study were consistent with another study conducted by Sidhu et al 12 conducted in a tertiary hospital in Punjab, whose findings revealed that majority of the participants (79.8%) had moderate stress levels, which in the current study was 55.5% of the samples. Wu et al 13 investigated to understand the job stress among young pharmacists working in the hospital during the COVID-19 period.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of the present study were consistent with another study conducted by Sidhu et al 12 conducted in a tertiary hospital in Punjab, whose findings revealed that majority of the participants (79.8%) had moderate stress levels, which in the current study was 55.5% of the samples. Wu et al 13 investigated to understand the job stress among young pharmacists working in the hospital during the COVID-19 period.…”
Section: Discussionsupporting
confidence: 92%
“…Statistically significant stress levels was found in female doctors (P=0.003) which was similar to the study conducted by Sidhu et al where a significant association between perceived stress level and female doctors were seen (P=0.009). 5 As a result of higher workload both at home and at work, female doctors are more stressed than male doctors. A significant association was also found between the chronic illness of the study participants and the stress level (p= 0.024).…”
Section: Discussionmentioning
confidence: 99%
“…4 Although the physical illness of doctors is at lower rates when compared to the general population, doctors have higher rates of suicide, psychiatric illness and possibly alcohol and drug misuse than the general population. 5 At an individual level, burnout among doctors has been associated with lower career satisfaction, higher absenteeism, greater probability of leaving the profession prematurely or choosing early retirement, and greater risk of experiencing difficulties in interpersonal relationships such as with family and partners. 5 In India only very few studies have evaluated psychological issues, stress and burnout among medical professionals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation